Analisa Tingkat Pemahaman Adat Istiadat Masyarakat Kenagarian Kinari Dengan Konsep Fuzzy Logic - Dhio Saputra; Irzal Arief Wisky (Universitas Pahlawan Tuanku Tambusai, 2018)
Kinari Nagari is one of the nagari in the Bukit Sundi sub-district, Solok regency which has Minangkabaucustoms that are still sustainable in the midst of community life, Kinari Nagari is also known as Nagari a thousand onerumah gadang with the customary application of basandi sarak, sarak basandi Kitabullah, which means community life isinseparable from harmony between customs and religion, kinari nagari has a tradition that is still thick, everything is seenin the daily lives of the people who still apply customary rules and norms of Minangkabau, which are seen in the way ofcommunication, daily behavior, the way to dress it all is written in the customary rules that exist in the village. Customsare cultural behaviors and rules that have been tried to be implemented in the community, with the existence of customscan have an impact on the behavior of the kinari nagari community. This research was conducted to analyze the level ofunderstanding of the kinari dancarian community customs. This research was conducted with the concept of fuzzy logicbased on artificial intelligent (AI).Keywords—customs, fuzzy logic, artificial intelligent.